2019
DOI: 10.1055/a-0960-9846
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Dysfunction in Schizophrenia and Aberrant Hippocampal Synaptic Plasticity in Rodent Model Psychosis: a Selective Review

Abstract: Schizophrenia is a complex, heterogeneous psychiatric disorder that affects about 1% of the global population. Hippocampal dysfunction has been linked to both cognitive deficits and positive symptoms in schizophrenia. Here, we briefly review current findings on disrupted hippocampal processing from a clinical perspective before concentrating on preclinical studies of aberrant hippocampal synaptic plasticity using the N-methyl-D-aspartate receptor hypofunction model of psychosis and related findings from geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 92 publications
1
4
0
Order By: Relevance
“…Bearing in mind the pivotal role of the subiculum as information gatekeeper between the hippocampus and other brain regions, this aberrant LTP in ventral subicular regularfiring neurons is expected to interfere with physiological hippocampal output processing. Thereby, our results add to the notion from previous rodent studies suggesting that subregion-specific reduced synaptic plasticity or aberrant hyperplasticity contributes to hippocampal dysfunction in firstepisode psychosis (Tamminga et al, 2012a;Bartsch et al, 2019). Moreover, our observation of a cell type-specific facilitation of subicular LTP after systemic NMDAR antagonism can be considered as a form of metaplasticity.…”
Section: Possible Functional Impact Of the Aberrant Noncanonical Ltp supporting
confidence: 86%
“…Bearing in mind the pivotal role of the subiculum as information gatekeeper between the hippocampus and other brain regions, this aberrant LTP in ventral subicular regularfiring neurons is expected to interfere with physiological hippocampal output processing. Thereby, our results add to the notion from previous rodent studies suggesting that subregion-specific reduced synaptic plasticity or aberrant hyperplasticity contributes to hippocampal dysfunction in firstepisode psychosis (Tamminga et al, 2012a;Bartsch et al, 2019). Moreover, our observation of a cell type-specific facilitation of subicular LTP after systemic NMDAR antagonism can be considered as a form of metaplasticity.…”
Section: Possible Functional Impact Of the Aberrant Noncanonical Ltp supporting
confidence: 86%
“…Accumulated studies have demonstrated that hippocampal and cortical LTP was impaired in both patients and animal models of schizophrenia, a fact that is thought to be closely correlated with the cognitive impairments (Bartsch et al, 2019;Stephan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…LTP is one of the core manifestations of synaptic plasticity and widely considered as a cellular basis of learning and memory (Lynch, 2004). Accumulated studies have demonstrated that hippocampal and cortical LTP was impaired in both patients and animal models of schizophrenia, a fact that is thought to be closely correlated with the cognitive impairments (Bartsch et al., 2019; Stephan et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…More broadly, our results suggest that reduced Ncan expression might contribute to an altered excitation-inhibition ratio hypothesized to be a key circuit mechanism in the major psychoses (Howes & Shatalina, 2022; Grent-’t-Jong et al, 2023), which, at a systems level, may be reflected by a manic phenotype (Miro et al, 2012) and tonically increased hippocampal activity (Bartsch et al, 2023; Assmann et al, 2021).…”
Section: Discussionmentioning
confidence: 76%